Visible to Mid-infrared Waveband Photodetector Based on Insulator Capped Asymmetry Black Phosphorous - Han, Qi; Jiang, Yadong; Han, Jiayue; Dong, Xiang; Gou, Jun (Frontiers in Physics, 2021)
Processing layer-dependent direct band gap and good absorption coefficient especially in the mid-infrared band, black phosphorous is believed to make a contribution superior to that of graphene in broadband photodetectors. The narrow band gap of 0.3 eV for bulk black phosphorous helps to absorb infrared radiation while a relatively large dark current under zero gate voltage is inevitable. Few layer black phosphorous sheets with asymmetrical thickness sealed in an insulator for protection is designed and explored for photosensitive mechanism in this work. Saturable absorption dominates the light harvesting process in visible light detection and thus limits maximum photocurrent to 3.3 and 1.4 μA for 520 and 650 nm lasers with a dark current of 0.7 μA. While in near-infrared wavelength, a responsivity of 0.12 A/W is inducted for 808 nm free of adsorption saturation even if the incident power is increased to 200 mW/cm2. Discrimination for the origin of the photo-response in short wavelength is conducted and the abnormal negative and nearly constant photocurrent in mid-infrared, irrelevant to inhomogeneous thickness, reveals the photothermal effect in a black phosphorous sheet. This work unravels various photoelectric features in black phosphorous and paves the way to designing more outstanding broadband photodetectors based on black phosphorous.